2009
DOI: 10.1007/s12193-009-0034-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-touch user interface evaluation for 3D object manipulation on mobile devices

Abstract: Multi-touch user interfaces (MTUIs) can represent a valuable tool for enhancing human-machine interaction. The naturalness and variety of hand gestures offer a more direct and intuitive form of interaction that can be exploited in a large spectrum of applications. Moreover, 3D visualization on mobile devices is a task required by increasing number of scenarios ranging from video games to engineering. In this paper, the impact of MTUIs when applied to 3D scene navigation on handheld devices is investigated. Num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In addition, we installed a separate application that enables us to easily extract the recorded data from the phone. 4 The interface of the CyanogenMod Android OS can refer to Fig. 3 (a).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we installed a separate application that enables us to easily extract the recorded data from the phone. 4 The interface of the CyanogenMod Android OS can refer to Fig. 3 (a).…”
Section: Data Collectionmentioning
confidence: 99%
“…The system uses the locations of these touch points to dynamically draw the grid of objects, and records pressure zones that are assigned to each finger. Fiorella et al [4] provided a preliminary study about multi-touch input (e.g., rotation, translation, and scaling) for 3D object manipulation on mobile devices. Their statistic analysis of 27 users on an iPod-touch device showed that their proposed multi-touch user interface could outperform the traditional button GUI.…”
Section: Related Workmentioning
confidence: 99%
“…Today's common solutions for interacting with VE with touch enabled devices mainly rely on multi-touch gestures or buttons to apply different camera transformations. It has already been shown that multi-touch gestures can surpass button based interactions [4]. When considering smartphones, multi-touch gestures imply that the user needs to hold the device with both hands, which can be tiresome and not always possible [1].…”
Section: Its 2014 • Postersmentioning
confidence: 99%
“…However new mobile devices are usually operated by the touch or multitouch interfaces. The 3D interaction has to be redefined in this new environment [5]. Table 1 presents summary of actions implemented for different interfaces.…”
Section: User Interaction In 3dmentioning
confidence: 99%